Urban Mobility And Tourism: Analyzing Millenial And Gen Z Travel Behavior For Sustainable Tourism Development - Sucipto; Siti Nuurlaily Rukmana (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2026)
Tourism development in Malang City is growing rapidly, driven by the preferences of Millennials and Generation Z who prioritize authenticity, digital connectivity, and sustainability. This study aims to analyze the mobility patterns of millennial and generation Z tourists and their implications for the sustainable development of urban tourism in Malang City, as well as the main factors influencing the choice and shift of tourists. These factors are focused on ease of access, availability and attractiveness of facilities, operational hours, and the existence of destinations on social media. This study also provides recommendations for sustainable urban tourism development in Malang City based on tourist mobility patterns. Spatial datasets were systematically compiled from Google Reviews, Google Points of Interest (POI), OpenStreetMap, and Strava to analyze the travel behavior of Millennials and Generation Z. The findings revealed that urban mobility patterns were concentrated in the districts of Klojen, Lowokwaru, and Blimbing, influenced by accessibility, facilities, operating hours, and social media visibility, especially TikTok. Gen Z’s mobility is highly correlated with social media exposure and artificial attractions, while Millennials are more influenced by operational hours and tourism infrastructure. The study recommends increasing digital promotion, improving facilities in high-traffic areas, and expanding tourism activities to suburban zones. These strategies aim to create a more inclusive, adaptive, and sustainable urban tourism experience that is aligned with the digital lifestyle and experience-oriented of the younger generation.